Treatment of Partial-Thickness Rotator Cuff Tears With a Resorbable Bioinductive Bovine Collagen Implant: 1-Year Results From a Prospective Multicenter Registry. Issue 8 (13th August 2021) - Bushnell, Brandon D.; Bishai, Shariff K.; Krupp, Ryan J.; McMillan, Sean; Schofield, Brian A.; Trenhaile, Scott W.; McIntyre, Louis F.
Background: Surgical treatment of partial-thickness rotator cuff tears remains challenging and controversial, with several traditional options including debridement with acromioplasty, transtendon or in situ repair, and take-down and repair. A resorbable bioinductive bovine collagen implant has shown promise as an alternative treatment option for partial-thickness tears. Purpose: Data from a registry were analyzed to further establish that the implant contributes to improved patient-reported outcome (PRO) scores across a large number of patients treated for partial-thickness rotator cuff tears. Study Design: Case series; Level of evidence, 4. Methods: A total of 19 centers in the United States enrolled patients >21 years old with partial-thickness tears of the rotator cuff in a comprehensive prospective multicenter registry. PRO scores were recorded preoperatively and postoperatively at 2 and 6 weeks, 3 and 6 months, and 1 year: American Shoulder and Elbow Surgeons, Single Assessment Numeric Evaluation, Veterans RAND 12-Item Health Survey (physical and mental component scores), and Western Ontario Rotator Cuff scores. Revisions were reported throughout the study. Results: The registry included 272 patients with partial-thickness tears (49 grade 1 tears, 101 grade 2 tears, and 122 grade 3 tears), 241 who underwent isolated bioinductive repair (IBR; collagen implant placed after bursectomy without a traditional rotator cuff repair), and 31 who had take-down and repair with bioinductive augmentation. Patients experienced statistically significant and sustained improvement from baseline for all PRO scores beginning at 3 months. Among patients with grade ≥2 tears, those with take-down and repair had significantly inferior scores at 2 and 6 weeks for most PRO scores as compared with those who underwent IBR, but the difference was no longer significant at 1 year for all but the physical component score of the Veterans RAND 12-Item Health Survey. There were 11 revisions, which occurred at a mean ± SD of 188.7 ± 88.0 days after the index surgery. There were no infections. Conclusion: This registry analysis further establishes across a large data set that this resorbable bioinductive bovine collagen implant improves PROs in all grades of partial-thickness tears, whether used as IBR or in conjunction with take-down and repair. IBR may offer improved early clinical outcomes (≤6 weeks) and comparable outcomes at 1 year when compared with a more invasive "take-down and repair" approach.